The effects of curing conditions on the performance and carbon dioxide emissions of fly ash-magnesium phosphate cement repair materials for pavement maintenance - Ying Su; Yelin Qian; Ming Sun; Changchun Li; Chunmei Liu; Dan Zhang; Xiaodong Zhang; Jun Yang; Yan Zhao; Rui Tao; Fengxia Xu (Journal of CO2 Utilization)
Magnesium phosphate cement (MPC) is a new type of repair material that is fast-setting, resistant to acids and alkalis, and environmentally friendly. Compared to commonly used repair materials and protective coatings, such as sulphoaluminate cement, epoxy resin, and zinc phosphate, MPC significantly reduces carbon dioxide emissions throughout its entire lifecycle (from raw material extraction to application, service, and waste disposal). Additionally, its advantages of fast curing, early strength, and excellent adhesion make it suitable for rapid repair of damaged roads and bridges. Furthermore, incorporating industrial by-products such as fly ash (FA) into MPC results in a cement that combines the advantageous properties of FA, offering excellent workability and durability. The substitution of FA for raw materials in MPC reduces the reliance on dead-burned MgO, contributing to a further reduction in CO2 emissions and lessening the impact on the natural environment. Studies have shown that MPC exhibits a decrease in strength under high humidity and water-curing conditions, and the addition of FA can help improve this phenomenon. However, the research lacks investigations on the effect of FA on the performance of MPC under different curing methods, with the same mix ratios and experimental conditions. This paper investigates the effects of FA content on MPC under standard curing conditions by measuring setting time, fluidity, and mechanical properties, as well as conducting microstructural characterization using XRD, FT-IR, and SEM. The results indicate that the addition of FA prolongs the setting time and decreases fluidity. Under standard curing conditions, the flexural strength after curing is higher than that under air curing, due to the formation of more gel-like products, which contribute to a denser microstructure favorable for the development of flexural strength. Moreover, standard curing conditions also promote the improvement of bonding strength. The bonding strength with the old substrate is higher than the flexural strength of FA-MPC itself, indicating that this material meets the requirements for the repair of highways and bridges. However, SEM analysis reveals that the moisture-rich curing environment may lead to cracking and damage in the hydration products of MPC, resulting in a reduction in compressive strength. The incorporation of FA enhances the mechanical properties of MPC through both the filling effect and pozzolanic activity, partially replacing MgO. Moreover, the addition of FA lowers the global warming potential (GWP) of MPC, reduces carbon emissions, and promotes more sustainable development.